Identifying the Components of Appointment of Library Managers - Samira Esmaeili; Saeid Asadi; Ali Sharafi (تحقیقات اطلاع‌رسانی و کتابخانه‌های عمومی, 2022)
Purpose: Libraries as one of the most important scientific, educational, research, social and cultural centers have an effective role in the development of information, awareness and human knowledge. However, the goals of libraries will not be accomplished without the appointment of capable managers to manage them efficiently. Thus the purpose of this study is to identify and introduce the components affecting the appointment of library managers based on previous research in this field. Method: This research is an applied study that has been carried out by descriptive method and documentary approach and content analysis. The statistical population of this research includes 62 articles, 7 books and 1 dissertation published in the field of library management. The data collection tool in this research is taking notes from published sources and the data analysis tool is Excel software. Findings: The findings showed that the components affecting the appointment of library managers include: “job/personal components” such as knowledge and professional information (work experience, years of service, completed training courses, related degree, scientific and administrative upgradability, and expertise), management skills (communication skills, decision-making and accountability, crisis management, teamwork, conflict management, delegation, time management, resource and capital management, creativity and innovation, identification and analysis of problems, understanding of individual differences, having the spirit of encouraging staff, foresight, commitment, and justice and fairness), personality traits (responsibility, self-confidence, tolerance, honesty and integrity, participatory spirit, neatness and orderliness, age, flexibility, and individual courage), attitude and insight (religious attitude, respect for subordinates, and precedence over relationship), public and professional reputation (informal communication, professional reputation, gaining employee trust, gaining superiors’ trust and clients’ trust); “organizational/internal factors” (structural dimension (organizational complexity, organizational formality, organizational centralization level, and budget system), and content dimension (organizational size, organizational culture, understanding of organizational goals and strategy, organizational technology, and leadership style of senior organizational managers)); “environmental/external factors” (general environment (social/cultural, geographical, economic, technological, political/legal factors) and specialized environment (organizational competitors, clients, and legal factors)). Originality/value: Appointment of library managers plays a very important role in their growth and prosperity. This research is one of the first descriptive and analytical studies in the field of library management that focuses on identifying and categorizing the components affecting the appointment of library managers and can lead to the identification and employment of talented and capable managers in libraries and increase the efficiency and effectiveness of libraries and information centers